Does economic shocks influence household's healthcare expenditure? Evidence from rural Nigeria - Rufai, Adedoyin Mistura; Ogunniyi, Adebayo; Abioye, Oyewale Daniel; Birindwa, Ahadi Bwihangane; Olagunju, Kehinde Oluseyi; Omotayo, Abiodun Olusola (Elsevier, 2021)
Health is profoundly influenced by several factors outside the traditional realm of healthcare. This paper employed a two-step Heckman selectivity model to examine factors influencing the decision to spend on health and the effects of economic shocks on health expenditure. The results from the first stage shows that the likelihood of spending on health increased with age, education, income, and decreases if the household is living in the northern region of Nigeria and uses mosquito bed-net. The findings from the second stage estimation show that a fall in the price of food items, an increase in the price of inputs for household enterprises and loss of job are the significant shocks that affect household health expenditure. Based on these findings, this study concluded that fall in the prices of major food items consumed within the household increased income available for health care among the farmers. Going forward, the study recommends the provision of holistic health-economic-welfare interventions for the marginalized rural populace in Nigeria.